ANALISIS PENGARUH DEGREE OF OPERATING LEVERAGE (DOL) TERHADAP RETURN ON ASSET (ROA) PADA PT. INDO KORDSA TBK - Kadafi Kadafi Kadafi; M. Rimawan (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
This research aims to know the effect of operating leverage against return on assets. The data in this study are data obtained from the website of the Indonesian Stock Exchange (IDX) authority with the population used in this study, especially the information on the Unified Monetary Position Report and the Articulation of Benefits and Misfortunes of 1990-2019 (29 years) of assembly organizations. The sample in this study was completed using the purposive sampling method to obtain the quantity of tests used in the examination from 2011-2019 (9 years). The results of this study indicate that the Operating Leverage projected with the Degree Of Operating Leverage (DOL) does not have a critical impact on Return On Assets.Keywords : Operating Leverage, Return On Asset